2012
DOI: 10.1095/biolreprod.111.093245
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Hoxa11 In Vivo in the Uterosacral Ligament and Uterus of Mice Results in Altered Collagen and Matrix Metalloproteinase Activity1

Abstract: Homeobox (HOX) genes are evolutionarily conserved genes encoding transcription factors that regulate mammalian embryonic growth and development of the urogenital tract. In both humans and mice, HOXA11 persists in the adult reproductive tract and is thought to play an important role in maintaining tissue developmental plasticity by regulating the expression of genes involved in extracellular matrix metabolism in the reproductive organs. Previously, we have shown that HOXA11 is necessary for development of the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…It is proposed that HOXA11 regulates the expression of genes involved in extracellular matrix metabolism. 55 Allen-Brady et al, 56 used genomewide association analysis on 2976 women and identified six single nucleotide polymorphisms (SNP) linked to POP. SNPs are very common mutations, occurring when a different nucleotide is substituted for the normal nucleotide in a DNA sequence.…”
Section: Regulators Of Collagenmentioning
confidence: 99%
“…It is proposed that HOXA11 regulates the expression of genes involved in extracellular matrix metabolism. 55 Allen-Brady et al, 56 used genomewide association analysis on 2976 women and identified six single nucleotide polymorphisms (SNP) linked to POP. SNPs are very common mutations, occurring when a different nucleotide is substituted for the normal nucleotide in a DNA sequence.…”
Section: Regulators Of Collagenmentioning
confidence: 99%
“…Ma and colleagues demonstrate that both TIMP1 and Timp2 decrease in the Hoxa11 KD mice. However, Timp1 was not affected, suggesting that TIMP1 was regulated at a posttranscriptional level [7].…”
mentioning
confidence: 91%
“…Thus, the study by Ma and others [7] represents a significant step in our understanding of female reproductive tissue remodeling. Their approach using a Hoxa11 KD [7] mouse model, with similar pelvic anatomy to humans [29], provides the foundation for elucidating the complex pathways of tissue remodeling that are critical to our understanding of female reproductive tract disorders. An important question to answer is: are the changes in collagens, MMP2, Timp2, and MMP9 an effect of attempted repair after injury or a cause of POP because of collagen destruction in the uterosacral ligament [12,26]?…”
mentioning
confidence: 98%
See 2 more Smart Citations